THE POLITICAL-STRATEGIC QUESTION OF PERU AS AN OBJECT OF SCIENTIFIC PRODUCTION AND COMMUNICATION IN THE CAEN-EPG: THE RESEARCH IN SECURITY, DEFENSE AND DEVELOPMENT - Vega Figueroa, Enver (2021)
The Centro de Altos Estudios Nacionales-Escuela de Posgrado (CAEN-EPG) is an institution of academic improvement, focused on the training and specialization of civil and military professionals regarding security, defense and development issues in Peru, and which leads to the obtaining master’s and doctorate degrees. According to the guidelines of the Peruvian university system, currently graduate institutions must be characterized by scientific production, in order to provide answers to knowledge problems. In this framework, this research aimed to present a conceptual approach to the political-strategic of Peru, since this is the object of academic and institutional research in the CAEN-EPG, in addition to uncovering the research methods and designs to build knowledge scientist on the situation of national security, defense and development, and propose some guidelines to make research production visible through a process of scientific communication. It should be noted that the Armed Forces, within the structure of the Peruvian State, participate in activities and actions directly related to aspects of security, defense, and national development, thus contributing to the socio-economic development of Peru; Therefore, effective scientific production in these areas will allow the communication of new knowledge that solves problems of a social nature, this being the main focus of the CAEN-EPG